Examen de auditoría integral al área de cuentas por cobrar de la empresa de Transportes Pavón Cía. Ltda., para el período 2013 - López Borja, Zoila Elizabeth (2015)
This work contains the theory of a Comprehensive Audit which comprises the Financial Audit, Internal Control, Compliance with Laws and Management, applied as practical to the Carrier Co. Pavón. Ltda., For which a component was selected based on their relevance, materiality and type of business entity for this reason we chose ACCOUNTS RECEIVABLE, which was applied in different proceeded according to the above approaches obtaining results presented in conjunction Integral Audit Report with appropriate recommendations to mitigate the findings and thus sufficient criterion is given to the management of the entity to make decisions to correct the weaknesses, shortcomings within the same avoiding future problems.